Evaluation of pre-selected challenges faced by black women smallholder farmers in Gauteng - Mhlongo, Fezeka (My University, 2019)
Researchers and policy makers agree that women, if given equal access to agricultural production resources, could contribute to the South African agricultural industry and economy. This study aimed to investigate certain challenges that prevent women farmers, specifically black female farmers, from growing their small-scale farms to the extent where they are able to become commercial farmers. The South African government has embarked on a number of initiatives to elevate and create a class of black commercial farmers; however, the efforts have yielded little progress. Challenges experienced by black women, are even more pronounced when looking at black emerging farmers and the government, along with industry stakeholders, has not been able to adequately address barriers of entry for black women. Insights from the study confirmed some of the pre-selected issues that were discussed in the literature review, especially in the South African context. Access to land, finance or credit, access to markets and access to extension support services were the most prominent challenges faced by the respondents. Based on the findings, recommendations include collaboration between financial institutions, government and other stakeholders to develop lending models suitable for emerging farmers, addressing land access and tenure limitations for black women and policy intervention for the regulation of food processing and quality standards to prevent emerging farmers from being barred from supplying higher end and more profitable markets. Keywords: Small-Scale Farmers, emerging farmers, black women, agriculture.
MBA
Keywords: Agriculture -- Economic aspects -- South Africa. Farms, Small -- South Africa.